LINGUISTIC ANALYSIS OF SOME ENGLISH PRAISING WORDS (International Conference on Modern Science and Scientific Studies, 2025)
This article investigates the linguistic characteristics of praising words in the English language. Praise as an essential part of human communication, plays a vital role in expressing admiration, approval, and positive evaluation. The study focuses on the semantic, morphological, syntactic, and pragmatic aspects of English praising words. It also explores how cultural values influence the use of praise in English-speaking communities. The findings demonstrate that English praising words not only serve as linguistic tools of politeness and encouragement but also reflect the sociocultural norms of English society.